Improved activity and SO2 tolerance of rare-earth elements modified CeTi catalyst for Hg0 and NO simultaneous removal from flue gas. Issue 2 (15th June 2022) - Long, Yifei; He, Zhong; Liu, Shinian; Zhou, Yongyan; Liu, Wenjie; Yin, Yajie; Tong, Xin; Li, Xiaoyi; Hu, Kang; Hu, Jiangjun
ABSTRACT: Six rare-earth elements (including La, Sm, Pr, Dy, Y, and Nd) were modified on the surface of the CeTi samples for Hg 0 oxidation and NO oxidation. The X-CeTi catalysts significantly improved the Hg 0 oxidation, NO oxidation, and SO2 tolerance compared with the CeTi catalyst. Moreover, O2 and NO can facilitate the activities significantly. The BET results showed that the specific surface area could be increased by doping of rare-earth elements. In addition, XRD and FT-IR experiments indicated that the rare-earth elements can facilitate the formation of the amorphous structure of CeO2 . The XPS curves of Ce 3d and O 1s showed that surface oxygen species and Ce 4+ /Ce 3+ redox couples were responsible for the catalytic performance, confirming that the SO2 tolerance was improved via the electron transfer by Ce 4+ +Dy 2+ â‡ŒCe 3+ +Dy 3+ reactions. The H2 -TPR results suggested that the redox capacity of X-CeTi catalysts was enhanced, which could improve the activities of the catalysts. Moreover, Dy-CeTi had the highest NO and Hg 0 oxidation among these rare-earth elements on account of the largest specific surface, more surface-active oxygen and H2 -TPR reduction peak integral area. The catalyst can maintain the conversion efficiency of elemental mercury and NO at 67% and 76% even in flue gas containing 800 ppm SO2 . Such work supplied new insights into modified Ce-Ti catalysts to simultaneously remove NO and elemental mercury from the flue gas with high efficiencies, which owned a promising prospect in the practical industrial application.